Penerapan Media Pembelajaran BIMA SI RAJA (Bisa Maca Sinau Aksara Jawa) Membaca Dan Menulis Aksara Jawa Pada Siswa Kelas VIII SMPN 2 Winong Pati - Rohmah, Naili Nur; Sulanjari, Bambang; Sunarya, Sunarya (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2026)
This study aims to describe the results of the application of the BIMA SI RAJA (Bisa Maca Sinau Aksara Jawa) learning media in learning to read and write Javanese script for class VIII of SMPN 2 Winong Pati. This is because students consider Javanese script very difficult to understand and difficult to understand by students because the form of Javanese script is almost similar and also students are not used to using Javanese script in everyday life. Another factor is caused by the teacher's delivery which only uses the lecture method and seems less varied. The teacher only provides an overview after which students are asked to work on the questions. The media used is also inadequate and less interesting which makes students seem less proficient in Javanese script. Thus, the formulation of the problem obtained is how the application and results of the BIMA SI RAJA (Bisa Maca Sinau Aksara Jawa) learning media. This research is included in pre-experimental design research in the form of a one-shot case study. The approach used in this study is a descriptive quantitative approach, because the data obtained are calculated statistically then the data are analyzed descriptively, namely describing the results of the data calculations. The data collection used in this study was purposive sampling, while the data obtained in this study were collected by interview and observation. After data analysis, the following results were obtained: 1) In the knowledge aspect, all students obtained scores above the Minimum Completion Criteria (KKM), with 15 students or 58% in the Very Good category with a value range of 88-100. And 11 students or (42%) were in the Good category with a value range of 75-87. 2) In the skills aspect, obtained scores above the Minimum Completion Criteria with 11 students or 42% in the Very Good category and 15 students or 58% in the Good category. Thus, the application of the BIMA SI RAJA (Bisa Maca Sinau Aksara Jawa) learning media in learning to read and write Javanese script for class VIII of SMPN 2 Winong Pati can have an influence on the learning outcomes that have been determined.